The dark side of AI innovation is supercharging disinformation and damaging democracy - Euractiv (Euractiv, 2025)
Misinformation and disinformation have always existed, but technological advancements have accelerated their impact. This Special Report looks at how AI misuse is damaging democracy.
Worldwide